2016
DOI: 10.1016/j.physe.2016.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Chiral vectors-tunable electronic property of MoS2 nanotubes

Abstract: The chirality plays a critical role in affecting the electronic property, wherein the armchair nanotube exhibits the indirect-band-gap and zigzag with direct-band-gap. The MoS 2 NTs with lower chiral vectors occupy the relatively higher carrier mobility for both armchair and zigzag types. The similarity of lattice parameters and formation energy implies a potential possibility of transition between two types of NTs with low index chiral vectors. a b s t r a c tIt has been demonstrated that the mechanical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…bulk TMDs [102]. In view of this and the tremendously larger cost associated with hybrids, PBE has been the functional of choice for TMD nanotubes [40,44,45,[47][48][49][50][52][53][54][55]. Note that the incorporation of spin-orbit coupling causes relatively minor modifications to the band structure [5], which is why it has been neglected here.…”
Section: Systems and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…bulk TMDs [102]. In view of this and the tremendously larger cost associated with hybrids, PBE has been the functional of choice for TMD nanotubes [40,44,45,[47][48][49][50][52][53][54][55]. Note that the incorporation of spin-orbit coupling causes relatively minor modifications to the band structure [5], which is why it has been neglected here.…”
Section: Systems and Methodsmentioning
confidence: 99%
“…This manifests itself into varying electronic properties encompassing semiconducting [31,32], metallic [33,34], and superconducting [35,36]. Notably, a number of mechanisms have been found to tune/tailor these properties, including chirality/radius [31,32,[37][38][39][40][41][42][43][44][45], defects [46,47], temperature [35,36], electric field [48,49], and mechanical deformation [50][51][52][53][54][55][56]. This makes TMD nanotubes ideally suited for a number of technological applications, including nanoelectromechanical devices [56][57][58], photodetectors [59][60][61], mechanical sensors [51,62,63], biosensors [64], and superconductive materials [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, theoretical studies suggested that small diameter nanotubes have a onedimensional band structure due to quantum confinement, 10 and we can tune the bandgap and enhance carrier mobility. 11 However, the one-dimensional nature of TMDC nanotubes has not been revealed yet because of difficulties in the synthesis of thin nanotubes with a uniform diameter and wall number. 12−15 It is important to develop a technique to prepare nanotubes with thin diameters in a relatively small distribution.…”
mentioning
confidence: 99%
“…Analogous to CNTs, these one-dimensional transition-metal dichalcogenide (TMDC) nanotubes have attracted much attention and prompted numerous studies because of their potential as lubricants and for optoelectronic devices and electrochemical hydrogen storage . MoS 2 NTs consist of a middle-Mo layer sandwiched between two S layers and can be classified as armchair or zigzag NTs based on their chiral vectors . Recently, a multilayer two-dimensional water structure confined in MoS 2 nanocavities has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…21 MoS 2 NTs consist of a middle-Mo layer sandwiched between two S layers and can be classified as armchair or zigzag NTs based on their chiral vectors. 22 Recently, a multilayer two-dimensional water structure confined in MoS 2 nanocavities has been reported. 23 Unlike graphene, water spontaneously fills the region sandwiched by two MoS 2 nanosheets at ambient conditions to form planar multilayered water structures.…”
Section: ■ Introductionmentioning
confidence: 99%